2018
DOI: 10.3748/wjg.v24.i4.504
|View full text |Cite
|
Sign up to set email alerts
|

Application value of enhanced recovery after surgery for total laparoscopic uncut Roux-en-Y gastrojejunostomy after distal gastrectomy

Abstract: AIMTo evaluate the safety and feasibility of enhanced recovery after surgery (ERAS) for total laparoscopic uncut Roux-en-Y gastrojejunostomy after distal gastrectomy.METHODSThe clinical data of 42 patients who were divided into an ERAS group (n = 20) and a control group (n = 22) were collected. The observed indicators included operation conditions, postoperative clinical indexes, and postoperative serum stress indexes. Measurement data following a normal distribution are presented as mean ± SD and were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…A flow diagram of the study selection process is shown in figure 1. A total of 445 studies were initially included but 12 RCTs with a total of 1216 patients were found to be eligible for the final meta-analysis 19 20 28–37. A total of 11 RCTs were published in English, whereas 1 RCT was published in Chinese.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A flow diagram of the study selection process is shown in figure 1. A total of 445 studies were initially included but 12 RCTs with a total of 1216 patients were found to be eligible for the final meta-analysis 19 20 28–37. A total of 11 RCTs were published in English, whereas 1 RCT was published in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…A random-effects model was used (p<0.00001, I 2 =91%) and there was a significant reduction of the first passage time of defecation in ERAS group compared with the control group (MD=−27.55, 95% CI −47.56 to 7.46, p=0.007) (figure 6). Twelve studies published the first passage time of flatus 19 20 28–30 32–34 37. There was significant heterogeneity among the trials (p<0.00001, I 2 =80%) and a significant reduction for the first passage time of flatus in the ERAS group compared with the control group (MD=−14.36, 95% CI −18.63 to 10.08, p<0.00001) (figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Se calculó la correlación de Spearman entre coste total y estancia total. El grado de satisfacción del paciente ha sido también relacionado con los programas de recuperación intensificada (186,187).…”
Section: Costes Y Morbilidad Análisis Multivarianteunclassified